Electrochemical production of colloidal sulphur by reduction of sulphur dioxide using a parallel plate reactor with convergent flow - Fornes, Juan Pablo (2015)
A parallel-plate electrochemical reactor with a double convergent flow at the cathodic and also at the anodic compartment is analysed for the production of colloidal sulphur by reduction of sulphur dioxide. A reactor with convergent flow was adopted in order to enhance the mass-transfer conditions along the electrode length. A mathematical treatment is presented for reactors with convergent flow based on the plug flow model, which can predict the maximum current. However, at higher times the cathode is blocked by the deposited sulphur decreasing the current. The best working conditions were achieved with a polished cathode working at a potential of –0.7 V against SCE for a volumetric flow rate of 8.33 × 10−6 m3 s−1 obtaining 19.6 kg m−3 h−1 as the maximum value of space time yield, for which the electrical parameters were 2.6 V average cell voltage, 22 kWh kg−1 specific energy consumption and 40 % current efficiency. The colloidal sulphur presents particles of spheroidal shape with an average diameter of 1.85 μm.